Implementation Design Interior Class ECD 5-6 Years Old Children in the Cognitive Development - Rifmasari, Yessi; S, Neviyarni (International Journal of Educational Dynamics, 2023)
The problem with this research was that many children have not been able to develop aspects of cognitive development. Therefore, an Early Childhood (ECD) class in interior design was conducted. The research purpose was to reveal the early childhood classroom interior design implementation in children aged 5-6 years cognitive development in Harapan Kita Kindergarten, Sungai Liku - Pesisir Selatan Regency. The research method used was descriptive qualitative. Data were collected through three activities, namely: interviews, observation, and documentation. The research results indicated that the planning and interior design of the ECD class. Data is obtained through the reduction of data, highlighting and choosing the key points, and concentrating ting on what's important. So that the research results show that the interior design of ECD is advantageous for kids between the ages of 5 and 6 and positively impacts children's cognitive development.